Perfusion CT – A novel quantitative and qualitative imaging biomarker in gastric cancer. Issue 95 (October 2017) - Kruk-Bachonko, Joanna; Krupski, Witold; Czechowski, Michał; Kurys-Denis, Ewa; Mądro, Przemysław; Sierocińska-Sawa, Jadwiga; Dąbrowski, Andrzej; Wallner, Grzegorz; Skoczylas, Tomasz
Highlights: P-CT assess neoangiogenesis in vivo and gastric cancer treatment effects. P-CT allows responding and noresponding patients selection (based on BF and PS). Tumor size reduction after therapy was significantly correlated with BF and PS. Neoadjuvant therapy was more effective in patients with higher baseline BF and PS. Abstract: Objectives: The aim of this research was to examine whether Perfusion Computed Tomography (P-CT) can qualitatively and quantitatively help detect gastric cancer neoangiogenesis in vivo as well as treatment response evaluation. We attempted to explore which P-CT parameters are best used in neoangiogenesis and neoadjuvant therapy for most effective evaluation. We also tried to recognize a positive prediction value of P-CT in early responders and non-responders patients identification. Materials and methods: Twenty-four patients with positive biopsy results and/or clinically proven gastric cancer were enrolled in the P-CT exam. Patients were qualified for systemic treatment (16 patients received chemotherapy and 8 patients received radiochemotherapy). The baseline Perfusion-CT exam and after neoadjuvant treatment Perfusion-CT exam were conducted using a 64-row GE tomograph based on a deconvolution model in first-pass protocol perfusion. The P-CT examined the following parameters: Blood Flow (BF), Blood Volume (BV), Mean Transit Time (MTT) and Permeability Surface (PS). Positive clinical response to neoadjuvant treatment (CHT and RCT) was defined as tumor size reduction 25% or more. Results: Tumor dimension reduction after neoadjuvant therapy was significantly correlated with the BF and the PS. Neoadjuvant therapy was more effective for patients with higher output BF and PS values. We did not register a significant relationship between BV and MTT parameters and tumor dimension reduction. Patients with a positive treatment response showed a decrease in BF, BV and PS perfusion parameters with an increase in MTT. Conclusions: P-CT examination allows a noninvasive neoangiogenesis assessment in vivo, leading to early identification of responding and non-responding patients. As a standard procedure, a full evaluation of treatment response should include a P-CT exam assessing neoangiogenesis.